Dimensions of psychotic experiences among women in the general population. Issue 1 (27th December 2013) - Therman, Sebastian; Suvisaari, Jaana; Hultman, Christina M.
Abstract Full‐information factor analysis of ordinal data was employed to determine the factorial structure of the responses of 31, 822 adult Swedish women to the 20 "positive" psychotic experience items of the Community Assessment of Psychic Experiences (CAPE) questionnaire. Five separable but correlated trait dimensions were found, reflecting Paranoia, Grandiosity, Magical Thinking, Delusions, and Hallucinations. High scores on any dimension were associated with a higher probability of questionnaire‐assessed lifetime major depressive episodes or generalized anxiety disorder, though Grandiosity was so only to a very small degree. Our results closely match previous findings among adolescents and young women, and demonstrate that psychotic experiences cannot be considered a single trait. Copyright © 2013 John Wiley & Sons, Ltd.